2019
DOI: 10.1111/iju.14154
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of malignant urachal tumor: A hospital‐based cancer registry data in Japan

Abstract: Objectives To identify the clinicopathological features of malignant urachal tumor in Japan, and analyze the 5‐year overall survival of malignant urachal tumor patients. Methods We used the hospital‐based cancer registry data to extract malignant urachal tumor cases that were diagnosed in 2008–2009 and 2012–2015, histologically confirmed, and received the first course of treatment. We analyzed the 5‐year overall survival using the 2008–2009 cohort’s data. Results We identified 456 patients, and malignant urach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…In contrast, higher proportions of UrC (approx. 2-fold) than BC cases have been reported for the Japanese population (0.4-0.6%) [18,26,31]. The reason for this phenomenon remains unclear and warrants further investigation.…”
Section: Discussionmentioning
confidence: 78%
“…In contrast, higher proportions of UrC (approx. 2-fold) than BC cases have been reported for the Japanese population (0.4-0.6%) [18,26,31]. The reason for this phenomenon remains unclear and warrants further investigation.…”
Section: Discussionmentioning
confidence: 78%
“…The present study by Nagumo et al contributes to this field by reporting the first population-based data from Japan. 6 The number of diagnosed UrC cases of 456 in a period of just 6 years appears to be higher than in other countries with available data, even when considering the population size of Japan. This assumption is in accordance with a previous Japanese study by Ghazizadeh et al, which reported a nearly twofold higher UrC incidence in Japan compared with Western countries.…”
mentioning
confidence: 77%
“…In this issue of International Journal of Urology , Nagumo et al. reported the clinicopathological features and outcome of urachal cancer using a hospital‐based cancer registry in Japan . They identified 456 patients with urachal cancer, which accounted for 0.4% of all malignant bladder cancers .…”
mentioning
confidence: 99%
“…Urachal adenocarcinoma (UrAC) arises in adults from the vestigial musculofibrous remnant band that connects the allantois and the bladder during embryonic development. A large proportion of patients with UrAC initially present with an advanced disease [7] and patients with metastatic urachal cancer have a poor prognosis [8][9][10][11]. Given the rarity of urachal cancers, prospective trials to guide the treatment of patients with advanced disease are lacking, there are no standard chemotherapeutic regimens, and surgery remains the mainstay of therapy shown to improve the overall survival outcome of UrAC [12].…”
Section: Introductionmentioning
confidence: 99%
“…Given the rarity of urachal cancers, prospective trials to guide the treatment of patients with advanced disease are lacking, there are no standard chemotherapeutic regimens, and surgery remains the mainstay of therapy shown to improve the overall survival outcome of UrAC [12]. To date, no randomized trials of urachal carcinomas have been reported and the most comprehensive reviews to date have concluded 420 [10] and 456 [11] patients reported regionally and 1010 patients reported globally [13]. As a result, limited information exists regarding the effective management of these cancers beyond the use of chemotherapy including 5-fluorouracil based, 5-fluorouracil and cisplatin [14][15][16][17] or hyperthermic intraperitoneal chemotherapy [18][19][20].…”
Section: Introductionmentioning
confidence: 99%